GISS Model E2.2: A Climate Model Optimized for the Middle Atmosphere—2. Validation of Large‐Scale Transport and Evaluation of Climate Response. Issue 24 (18th December 2020) - Orbe, Clara; Rind, David; Jonas, Jeffrey; Nazarenko, Larissa; Faluvegi, Greg; Murray, Lee T.; Shindell, Drew T.; Tsigaridis, Kostas; Zhou, Tiehan; Kelley, Maxwell; Schmidt, Gavin A.
Abstract: Here we examine the large‐scale transport characteristics of the new "Middle Atmosphere" NASA Goddard Institute for Space Studies (GISS) climate model (E2.2). First, we evaluate the stratospheric transport circulation in historical atmosphere‐only simulations integrated with interactive trace gas and aerosol chemistry. Compared to lower vertical resolution model versions, E2.2 exhibits improved tropical ascent and older stratospheric mean ages that are more consistent with observed values. In the troposphere, poleward transport to the Arctic and interhemispheric mean ages in E2.2 are comparable to models participating in the Chemistry Climate Modeling Initiative. In addition to validating E2.2, we also assess its "transport sensitivity" using the coupled atmosphere‐ocean abrupt 4xCO2 and transient 1%CO2 simulations submitted to the Coupled Model Intercomparison Project, Phase 6, along with a 2xCO2 simulation used to evaluate the linearity of the transport circulation's response to increased CO2 . We show that decreases (increases) in a stratospheric mean age (idealized surface loss) tracer scale linearly with increased lower stratospheric upwelling, which also increases linearly with warming tropical sea surface temperatures (SSTs). Abrupt 2xCO2 and 4xCO2 experiments constrained with (fixed) pre‐industrial SSTs are also used to quantify the relative importance of rapid adjustments versus SST feedbacks to the transport circulation responses in the model. Finally, sensitivity experiments are presented to illustrate the impact of changes in the convective parameterization on stratospheric transport. Key Points: New GISS "high‐top" climate model features significantly improved stratospheric transport properties compared to previous model versions The stratospheric transport circulation responds more or less linearly to increased CO2 SST feedbacks dominate the lower stratospheric (80 hPa) transport response to CO2 while rapid adjustments are more important above (10 hPa)